2013
DOI: 10.1007/s00384-013-1759-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic distribution of cancers and colorectal adenomas according to age and sex and relationship between proximal and distal neoplasms in an i-FOBT-positive average-risk Italian screening cohort

Abstract: A left to right shift of colorectal adenomas with increasing age is evident in northern Italian asymptomatic i-FOBT-positive population. Advanced proximal neoplasms are not uncommon in subjects with or without distal adenomas, especially after 60 years of age. This should be carefully considered when implementing public screening strategies for CRC since the use of flexible sigmoidoscopy as a screening tool, particularly in older age groups, appears to be less effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
3
6
0
1
Order By: Relevance
“…Concerning the differences between RC and LC regarding the populations, our results support those of a systematic review [13] and two epidemiological studies [14,15] that found that the origin of colon cancer shifted from left to right with increasing age. In respect of the postsurgical course, our results support the general belief that LC is associated with more postoperative complications than RC, but they differ from data presented by other authors regarding the subgroups of complications and LOS.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the differences between RC and LC regarding the populations, our results support those of a systematic review [13] and two epidemiological studies [14,15] that found that the origin of colon cancer shifted from left to right with increasing age. In respect of the postsurgical course, our results support the general belief that LC is associated with more postoperative complications than RC, but they differ from data presented by other authors regarding the subgroups of complications and LOS.…”
Section: Discussionsupporting
confidence: 93%
“…16 The proximal shifting of colon cancer has been shown to be related to increasing age in an Italian population. 17 Based on our observations, the proximal shift of colonic cancer may not have started yet in area with lower cancer incidence in China. This is further supported by our multivariate analysis that living in Hong Kong is a risk factor associated with development of right-sided colonic cancer.…”
Section: Discussionmentioning
confidence: 74%
“…Colonic polyps are mostly classified on the basis of their properties to progress to malignancy (hyperplastic or adenomatous) as well as their structure including types (sessile, pedunculated, and flat), shape (tubular, villous, serrated) and size (small 1–5 mm, medium 5–10 mm, and large ≥ 10mm) [5]. Hyperplastic polyps are usually small, located in the rectum and sigmoid colon, and are generally thought to have no malignant potential.…”
Section: Introductionmentioning
confidence: 99%